Pollen, phytolith and starch analyses of dryland soils from Easter Island (Rapa Nui) show widespread vegetation clearance and Polynesian-introduced crops. (3rd July 2017) - Horrocks, Mark; Baisden, Troy; Flenley, John; Feek, David; Love, Charles; Haoa-Cardinali, Sonia; González Nualart, Lilian; Edmunds Gorman, Tahira
ABSTRACT: To investigate the extent of ancient agriculture on Easter Island, this study examines pollen, phytoliths and starch preserved in dryland soils at 11 sites across the island. Taxa are variably represented by different types of microfossils, with Arecaceae and Poaceae over-represented, and dicotyledons, Cyperaceae and ferns under-represented. Phytoliths show better preservation than pollen. The identification of four Polynesian-introduced cultigens, at seven sites, provides botanical evidence for island-wide horticulture. The cultigens identified, Broussonetia papyrifera, Colocasia esculenta, Ipomoea batatas and Musa sp., have differential representation in microfossil spectra, partly because of variable production of microfossil types and amounts, which could give a false impression of the importance of past species. The identification of phenolic inclusions represents a new microfossil type for C. esculenta. Large differences in microfossil proportions at one of the two high-altitude sites compared with low-altitude sites provide evidence for impact of the higher altitude climatic conditions on cropping across Easter Island.